Profil Pemecahan Masalah Sistem Persamaan Linear Dua Variabel Siswa SMAN 1 Sindue Ditinjau Dari Kecerdasan Emosional Tinggi - Adryana Smita; Maxinus Jaeng; Sudarman Bennu (Mitra Sains, 2019)
This study aimed to obtain a profile solving linear systems of equations of two variables at SMAN 1 Sindue terms of high emotional intelligence. This research is a qualitative research. The research subject is obtained from tests of emotional equotient. The subjects used in this study wasone studentistaken out of grade X students who have high emotional equotient (SEQT). The results of the study at this stage of understanding the problem, (1) SEQT able to write and mention the known and asked, identify the unknown with the sentence statement and asked the interrogative sentence or order,provide examples of known and asked to use their own words, have confidence high and quiet in understanding the problem; (2) SEQT plan calmly problem solving using elimination and substitution; (3) SEQT implement planned seriously and not in a hurry using of elimination and substitution with a relatively short time; (4) SEQT check all the answers that made carefully. After getting the final results and validate the answers then believe that their results are correct, have high self-confidence, more calm and able to adapt to the social environment.